2005
DOI: 10.1108/09555340510607361
|View full text |Cite
|
Sign up to set email alerts
|

Creating strategic capabilities: organizational learning and knowledge management in the new economy

Abstract: PurposeThe purpose of this paper is to contribute to the knowledge management and organizational learning literatures by clarifying the concepts and presenting a framework illustrating their relationship. The framework is meant to reduce confusion about learning and knowledge management issues and guide the design of international studies and data analysis.Design/methodology/approachConceptual discussion and approach are undertaken. The discussion focuses on the extrapolation of the current situation into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 37 publications
2
43
1
10
Order By: Relevance
“…Given the 'stickiness' of knowledge (Von Hippel, 1994), its elusiveness, complexity and resistance to definition (Tsoukas & Vladimirou, 2001), it is unsurprising that a broad range of organisational knowledge theories and management approaches have emerged in recent years (Baets, 2005;Choo & Bontis, 2002;Dimitriades, 2005). Nevertheless, however difficult it is to define, capture or manage, the desired outcome for organisations is to bring about changed understandings in their employees, as individuals, collectively and as organisational units.…”
Section: Crises Dmos and Knowledge Managementmentioning
confidence: 99%
“…Given the 'stickiness' of knowledge (Von Hippel, 1994), its elusiveness, complexity and resistance to definition (Tsoukas & Vladimirou, 2001), it is unsurprising that a broad range of organisational knowledge theories and management approaches have emerged in recent years (Baets, 2005;Choo & Bontis, 2002;Dimitriades, 2005). Nevertheless, however difficult it is to define, capture or manage, the desired outcome for organisations is to bring about changed understandings in their employees, as individuals, collectively and as organisational units.…”
Section: Crises Dmos and Knowledge Managementmentioning
confidence: 99%
“…Authors that cited components mentioned above are: Fredrickson (1983), Hax and Majluf (1991), Schmidt (1995), Podnar (2005), Manderscheid (2005), Dimitriades (2005), Bayerlein (2005), Melewar and Karaosmanoglu (2006), and Service (2006).…”
Section: Methodology: the Firms Under Studymentioning
confidence: 99%
“…Handzic [21] emphasises that even the GO's complex interactions influences the knowledge stocks of the organisation. Three studies on the Malaysian government showed a need for knowledge sharing practices, after knowledge economy strategy that was set ten years ago [10] [22]. Another work in Pakistan GO's recently carried by Abbass et al [23] revealed a significant high relationship between the complexity of the government organisation practices and KM practices.…”
Section: Km Influence On Government Organizations and Their Initiativesmentioning
confidence: 99%
“…OL represent the capacity to change, through continuous improvement that is based on lessons learned from mistakes and learning from best practices [31]. OL is argued to be the source of organisational capability that can enhance the areas of experimentation, risk taking, external environment interaction and participative decision-making that lead to better organisational dialogue [10]. Chawla and Joshi [1] note that even the KM best practices can create OL for improving governmental organisation performance.…”
Section: Km Influence On Organisational Learningmentioning
confidence: 99%
See 1 more Smart Citation